Complications of Kidney Biopsy in a Tertiary Hospital of Central Nepal, Chitwan - Ghimire, Madhav; Vaidya, Shreeju; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2020)
Background: Kidney biopsy is an important diagnostic tool in Nephrology and is said to berelatively a safe procedure.There are limited studies in the complications of kidney biopsy from this region. We therefore thought of looking into the complications of kidney biopsy and its risk factors. Methods: A hospital based analytical cross sectional study was carried out over a period of 3 years. Kidney biopsies were done under ultrasonography guidance. The complications and its risk factors were recorded and were analyzed using mean, standard deviation, ratio, percentage and chi square. Results: A total of 210 patients were analysed. The mean± standard deviation of 210 patients was 35.7±14.9 years. The commonest minor complication was biopsy site pain not requiring analgesics 136 (64.8%)and the commonest major complication was biopsy site pain requiring analgesics 18(8.6%) followed by perinephric hematoma 10 (4.8%).There was a significant association between low platelet count and the development of complications like pain requiring analgesic (p value 0.04), perinephric hematoma (p value 0.022) and gross hematuria (p value 0.011). Conclusions: Kidney biopsy is a safe procedure and low platelet count is a significant risk factor for complications (p value <0.05). Keywords: complications; kidney biopsy; perinephric hematoma; platelet count.